Book of Anonymity - Anon Collective (punctum books, 2021)
Anonymity is highly contested, marking the limits of civil liberties and legality. Digital technologies of communication, identification, and surveillance put anonymity to the test. They challenge how anonymity can be achieved, and dismantled. Everyday digital practices and claims for transparency shape the ways in which anonymity is desired, done, and undone. The Book of Anonymity includes contributions by artists, anthropologists, sociologists, media scholars, and art historians. It features ethnographic research, conceptual work, and artistic practices conducted in France, Germany, India, Iran, Switzerland, the UK, and the US. From police to hacking cultures, from Bitcoin to sperm donation, from Yik-Yak to Amazon and IKEA, from DNA to Big Data - thirty essays address how the reconfiguration of anonymity transforms our concepts of privacy, property, self, kin, addiction, currency, and labor.